Efficacy of insecticides in fruit borer control and residues on sugar apple fruit - Alessandro da Silva Oliveira (Revista Ceres)
ABSTRACT Bahia is the Brazilian state with the largest production of sugar apple fruits (Annona squamosa L.), and fruit borer (Cerconota anonella, Sepp. 1830) is a key crop pest. Insecticides are the main strategy for pest control even though there are no pesticides registered for this crop. This study aimed to assess the efficacy of insecticides to control fruit borer and determine the levels of insecticide residues in sugar apple fruits aiming at requesting the extension of authorization to use insecticide products in this crop. The experiment was conducted in an eight-year-old irrigated orchard (2 × 4 m) located in Anagé, Bahia, Brazil. The experimental design was a randomized block design with 10 treatments (three insecticides with three doses and a control with water) and 5 replications. Each plot was composed of four plants but only the two central ones were assessed. Insecticides and doses (g a.i. 100 L−1 water) were Bacillus thuringiensis: 0.8, 1.7, and 2.5; triflumuron: 2.4, 3.6, and 4.8; and imidacloprid: 4.0, 10.0, and 16.0. Nine sprayings were carried out at fortnightly intervals with a costal sprayer with constant pressure, JA-2 nozzle, and with jet directed to the fruits. Ten assessments were performed in order to observe fruit borer presence in 30 previously marked fruits per plot. Imidacloprid, at the highest studied dose, was the only effective treatment. Analyses of imidacloprid residues, at 21 and 30 days after the highest dose application, indicated levels higher than the maximum limit allowed. Insecticides under the conditions tested do not meet the norms for requesting the extension of authorization to use insecticides for citrus in sugar apple fruits.